2013
DOI: 10.1002/jib.82
|View full text |Cite
|
Sign up to set email alerts
|

A study of beer bitterness loss during the various stages of the Romanian beer production process

Abstract: Beer is one of the oldest known alcoholic beverages produced by a yeast fermentation of a cereal extract that was germinated in water beforehand. The bitter taste of beer comes from the group of substances introduced during wort boiling, which are the extracted components of hops. The aim of this study was to determine some characteristics of beer (original extract, alcohol content, colour, pH, total acidity, carbon dioxide and bitterness values) during the three stages of the beer production process in a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 14 publications
3
34
1
2
Order By: Relevance
“…All styles of blue corn malt beers showed a significant decrease in bitterness units during the steps of the process, except for style 3. The observed behaviour coincides with that reported by Popescu et al (31), who observed that the bitterness value gradually decreased during the process (boiling, fermentation and bottling), with values of bitterness units of 32-35 for wort, 23-26 for green beer and 18-21 for light mature barley beer.…”
Section: Chemical Parameters In the Process Stagessupporting
confidence: 90%
See 1 more Smart Citation
“…All styles of blue corn malt beers showed a significant decrease in bitterness units during the steps of the process, except for style 3. The observed behaviour coincides with that reported by Popescu et al (31), who observed that the bitterness value gradually decreased during the process (boiling, fermentation and bottling), with values of bitterness units of 32-35 for wort, 23-26 for green beer and 18-21 for light mature barley beer.…”
Section: Chemical Parameters In the Process Stagessupporting
confidence: 90%
“…Total acidity (Fig. 1D) in mature beers was found to range between 0.18 and 0.26 g lactic acid/100 mL, which corresponds to 0.12 and 0.17 g acetic acid/100 mL; these values were lower than the values reported by Popescu et al (31), who reported total acidity values of 2.7-3.2 g acetic acid/L for light beers and 3.8-4.1 for dark barley beers. A significant difference in total acidity was observed for all BCMB styles except styles 5 and 6 during the three steps of the process.…”
Section: Chemical Parameters In the Process Stagescontrasting
confidence: 62%
“…Bubbles of CO 2 were released from the beer, which was visible by the production of foam. After half an hour, the foam disappeared, an indication that the beer did not contain CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[23] Bitterness The determination of bitterness was carried out according to the accepted methodology by the European Brewery Convention (E.B.C.). [11,24] The values were expressed in E.B.C. units (EBU).…”
Section: Alcohol Contentmentioning
confidence: 99%
“…[9,11] Therefore, the detailed beer characterization is costly and time-consuming. Moreover, these quality attributes of beers are related to the occurrence of specific molecule families in the beverage.…”
Section: Introductionmentioning
confidence: 99%